The role of nurse in postoperative pain management - Juszczak, Katarzyna (Pielęgniarstwo Chirurgiczne i Angiologiczne/Surgical and Vascular Nursing, 2009)
An essential element of proper post-operative treatment is effective pain therapy, as pain brings a much increased risk of adverse reactions and prolongs the period of return to full health. Despite progress in knowledge of pathophysiology of pain, analgesia and pharmacological resources and better methods of treatment in clinical practice, many patients still suffer pain in the postoperative period. The treatment of pain has for a long time not been given due weight, which resulted in that it was regarded by patients and physicians as a necessary component of the post-operative period. Using the current state of knowledge of available medicines and treatments the fight against post-operative pain can be effective. A key role in the fight against post-operative pain is played by the nurse. The nurse has a special role in the treatment of pain, because she spends most time at the bedside and the patient has the possibility of careful observation.